Fluorinated Tetraarylethenes: Universal Tags for the Synthesis of Solid State Luminogens. Issue 48 (26th October 2022) - Suleymanov, Abdusalom A.; Kraus, Barbara M.; Damiens, Thibault; Ruggi, Albert; Solari, Euro; Scopelliti, Rosario; Fadaei‐Tirani, Farzaneh; Severin, Kay
Abstract: The aggregation‐induced emission properties of tetraarylethenes (TAEs) have led to numerous applications in chemistry, biology, and materials science. Herein, we describe two fluorinated tetraarylethenes, which can be employed as universal tags for the synthesis of solid state luminogens. The tags are accessible in one or two steps from commercially available starting materials. Facile coupling reactions with ubiquitous substrates such as thiols, alcohols, amines, phosphines, aldehydes, and enamines allow preparing a wide range of TAE conjugates, including tagged amino acids, peptides, carbohydrates, steroids, and commercial polymers. Abstract : A simple method for the coupling of fluorinated tetraarylethens to a wide range of substrates is described. The approach allows converting amino acids, bioactive compounds, carbohydrates, steroids, and polymers in one step into solid state luminogens.